2011
DOI: 10.1210/me.2010-0409
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Depletion-Insensitivity of Prostate Cancer Cells Is Supported by the AR Without Binding to Classical Response Elements

Abstract: A need for androgen response elements (AREs) for androgen receptor (AR)-dependent growth of hormone depletion-insensitive prostate cancer is generally presumed. In such cells, androgen-independent activation by AR of certain genes has been attributed to selective increases in basal associations of AR with putative enhancers. We examined the importance of AR binding to DNA in prostate cancer cells in which proliferation in the absence of hormone was profoundly (∼ 90%) dependent on endogenous AR and where the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…genes strikingly overlaps the signature gene overexpression profile of clinical castration-recurrent prostate tumors and is enriched for gene clusters primarily supporting mitotic cell division (9,20). Furthermore, we have demonstrated that in those cells the AR apoprotein can support growth through gene activation that occurs without the direct binding of AR to AREs and likely through tethered associations of the receptor with its target genes (9).…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…genes strikingly overlaps the signature gene overexpression profile of clinical castration-recurrent prostate tumors and is enriched for gene clusters primarily supporting mitotic cell division (9,20). Furthermore, we have demonstrated that in those cells the AR apoprotein can support growth through gene activation that occurs without the direct binding of AR to AREs and likely through tethered associations of the receptor with its target genes (9).…”
mentioning
confidence: 62%
“…Furthermore, we have demonstrated that in those cells the AR apoprotein can support growth through gene activation that occurs without the direct binding of AR to AREs and likely through tethered associations of the receptor with its target genes (9). Our previous detailed studies of the interaction of AR with CCAAT/enhancer-binding protein ␣ (involved in terminal tissue differentiation) suggested that tethered associations of AR with DNA may not require hormone except in cell contexts in which androgen is needed for nuclear import of AR (21).…”
mentioning
confidence: 96%
See 3 more Smart Citations